The The Influence of Social Media Content and Word of Mouth in The Decision of Choose Places to Study Of 'Aisyiyah University Yogyakarta - Erpiyanti; Rahmawati, Fitri Maulidah (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The title of the research is the influence of social media content and word of mouth on the decision to choose a place to study. Today education is an obligation that must be taken before entering the world of work. One of the barometers of national education is the Special Region of Yogyakarta. 'Aisyiyah Yogyakarta University is one of the many tertiary institutions in the Special Region of Yogyakarta. Even though it is only a university, 'Aisyiyah Yogyakarta University is able to compete with other private universities in Yogyakarta. Promotions carried out by 'Aisyiyah Yogyakarta University to convey information about the campus are carried out by uploading content on social media and word of mouth. This study aims to examine the effect of social media content and word of mouth on the decision to choose a place to study at 'Aisyiyah University, Yogyakarta. This research is a type of quantitative research with snowball sampling technique. The sample used is active students of 'Aisyiyah University, Yogyakarta. The research instrument used was a questionnaire distributed online.